Paleoceanography and ice sheet variability offshore Wilkes Land, Antarctica - Part 2: Insights from Oligocene-Miocene dinoflagellate cyst assemblages - Bijl, Peter K.; Houben, Alexander J. P.; Hartman, Julian D.; Pross, Jörg; Salabarnada, Ariadna; Escutia, Carlota; Sangiorgi, Francesca (Climate of the past, 2018)
Abstract. Next to atmospheric CO2 concentrations, ice-proximal oceanographic conditions are a critical factor for the stability of Antarctic marine-terminating ice sheets. The Oligocene and Miocene epochs (∼ 34-5 Myr ago) were time intervals with atmospheric CO2 concentrations between those of present-day and those expected for the near future. As such, these past analogues may provide insights into ice-sheet volume stability under warmer-than-present-day climates. We present organic-walled dinoflagellate cyst (dinocyst) assemblages from chronostratigraphically well-constrained Oligocene to mid-Miocene sediments from Integrated Ocean Drilling Program (IODP) Site U1356. Situated offshore the Wilkes Land continental margin, East Antarctica, the sediments from Site U1356 have archived the dynamics of an ice sheet that is today mostly grounded below sea level. We interpret dinocyst assemblages in terms of paleoceanographic change on different timescales, i.e. with regard to both glacial-interglacial and long-term variability. Our record shows that a sea-ice-related dinocyst species, Selenopemphix antarctica, occurs only for the first 1.5 Myr of the early Oligocene, following the onset of full continental glaciation on Antarctica, and after the Mid-Miocene Climatic Optimum. Dinocysts suggest a weaker-than-modern sea-ice season for the remainder of the Oligocene and Miocene. The assemblages generally bear strong similarity to present-day open-ocean, high-nutrient settings north of the sea-ice edge, with episodic dominance of temperate species similar to those found in the present-day subtropical front. Oligotrophic and temperate surface waters prevailed over the site notably during interglacial times, suggesting that the positions of the (subpolar) oceanic frontal systems have varied in concordance with Oligocene-Miocene glacial-interglacial climate variability.
Gesehen am 14.08.2019